Terapia celular com células mononucleares de medula óssea previne a disfunção ventricular esquerda em modelo de sobrecarga volumétrica em ratos? - Miranda, Victor Hugo Martins de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Heart failure (HF) is the end stage of different cardiac diseases including volume overload associated to aortic regurgitation (AR). Due to high mortality related to HF, alternative therapies using stem cell (SC) contained in bone marrow mononuclear cells (BMMNC) portion have been investigated. Since the cardiac regeneration hypothesis by SC has been debated and considering that different mechanisms (cytoprotective, antiinflammatory and antifibrotic action) have been suggested, the use of SC in cardiac disease model without significant tissue loss becomes relevant. Within this context, the present study aims to investigate the effect of BMMNC intramyocardial administration (im) on remodeling and cardiac autonomic balance in AR Wistar rats. BMMNC were obtained from total bone marrow by ficoll gradient. The AR was induced experimentally and confirmed by echocardiography (ECHO) one week after. The animals were randomly assigned to im administration of DMEM (control) or BMMNC (5x106 cells/100 μL). SHAM animals were used for normal parameters acquisition. Echocardiographic evaluations were obtained at pre treatment (1 week after AR)and in the 3th and 7th week after treatment by im administration. In 7th week blood pressure and heart heat were recorded aiming to obtain the baroreflex sensitivity and the evaluation of autonomic tonus. At the final of the study, the heart was collected for analyses of the fibrosis percentage. After 1 week of AR induction (ECHO pré-treatment), we observed left ventricle (SI) and left atrium (LA/Ao) dilatation and the hypertrophy (HI) in the groups AR+DMEM (SI= 0,85±0,03; LA/Ao= 1,65±0,17; HI=0,77±0,07 cm3 /kg) when compared (p<0,05) with the SHAM ( SI= 0,62±0,03; LA/Ao=1,28±0,08; HI=0,58±0,04 cm3/kg). Therefore, the groups with AR departed from the same degree of dysfunction. After 3 weeks, we observed that the i.m administration of BMMNC didn't change the ECHO parameters when compared to DMEM im...

A insuficiência cardíaca (IC) é o estágio final de diferentes doenças cardíacas incluindo a sobrecarga volumétrica decorrente de insuficiência aórtica (IAo). Devido à alta taxa de mortalidade, terapias alternativas utilizando célula-tronco (CT) contidas na porção de células mononucleares da medula óssea (CMMO) têm sido investigadas. Uma vez que ahipótese de regeneração cardíaca com uso de CT tem sido debatida e quediferentes mecanismos (ação citoprotetora, antifibrótica e anti-inflamatória)têm sido aventados, a utilização de CT em modelo de doença cardíacasem perda tecidual significativa torna-se pertinente. Dentro deste contexto, a atual proposta visou investigar o efeito da administração intramiocárdica (im) de CMMO sobre o processo de remodelamento e balanço autonômico cardíacoem ratos Wistar com IAo. Para tanto as CMMO foram obtidas a partir da medula óssea total por gradiente de ficoll. A IAo foi induzida experimentalmente e confirmada por ecocardiografia após uma semana da indução. Os Animais foramsubmetidos aleatoriamente à administração im de DMEM ou CMMO (5x106 células/100 μL). Animais SHAM foram utilizados como padrão de normalidade. Foram feitas avaliações ecocardiográficas pré-tratamento (1 semana após IAo) e na 3ª e 7ª semana após tratamento por administração im. Na 7ª semana foram feitos registrosde pressão arterial e frequência cardíaca para obtenção da sensibilidade do barorreflexo e avaliação dotônus autonômico. Ao final do estudo o coração foi coletado para análise do percentual de fibrose. Após a 1ª semana de indução de IAo (ECO pré-tratamento), observamos dilatação de ventrículo (IE) e átrio esquerdo (AE/Ao) bem como hipertrofia (IH) nos grupos IAo+DMEM (IE: 0,78±0,06; AE/Ao: 1,65±0,17; IH: 0,77±0,07 cm3/kg) e IAo+CMMO (IE: 0,85±0,03; AE/Ao: 1,72±0,10; IH: 0,70±0,08 cm3/kg) quando comparados (p<0,05) ao SHAM (IE: 0,62±0,03; AE/Ao: 1,28±0,08;...
Keywords: Coração - Doenças; Barorreflexo; Células da medula óssea; Ecocardiografia; Insuficiência aórtica; Aortic valve insufficiency